2019
DOI: 10.1038/s41438-019-0201-z
|View full text |Cite
|
Sign up to set email alerts
|

Gene characterization and molecular pathway analysis of reverse thermosensitive genic male sterility in eggplant (Solanum melongena L.)

Abstract: The naturally occurring mutant eggplant line 05ms was identified with reverse thermosensitive genic male sterility (rTGMS), but its temperature-responsive fertility mechanisms remain largely unknown. Here, we studied the flower morphology, anther cellular structure, and genome-wide gene expression of this rTGMS line. Candidate genes for thermosensitive male sterility during the microspore development of 05ms and the temperature-insensitive line S63 under low-temperature (LT) and high-temperature (HT) condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In our study, 8 DEGs (PAL, C4H, CCR, and LAC) were up-regulated in roots related to lignin biosynthesis and achieved the highest expression level after 3 h Cd treatment. Increased lignin synthesis in roots to block Cd into the plant cells has also been identified in Vicia sativa [50], Brassica chinensis (B. chinensis) [47], Solanum melongena [51], Nicotiana species [52], and S. nigrum [10] under Cd stress. In addition, POD could regulate the biosynthesis of lignin and the related genes were upregulated in our studies [37,48].…”
Section: Discussionmentioning
confidence: 88%
“…In our study, 8 DEGs (PAL, C4H, CCR, and LAC) were up-regulated in roots related to lignin biosynthesis and achieved the highest expression level after 3 h Cd treatment. Increased lignin synthesis in roots to block Cd into the plant cells has also been identified in Vicia sativa [50], Brassica chinensis (B. chinensis) [47], Solanum melongena [51], Nicotiana species [52], and S. nigrum [10] under Cd stress. In addition, POD could regulate the biosynthesis of lignin and the related genes were upregulated in our studies [37,48].…”
Section: Discussionmentioning
confidence: 88%
“…Many previous studies have shown that heat stress can lead to male sterility in Oryza sativa L., Solanum melongena L., and Solanum lycopersicum Lam 44,45 . For example, in heat-susceptible rice plants, heat stress lasting 4 days or longer during the early phase of anther development caused the premature degradation of tapetum cells and PCD, leading to complete male sterility 46, 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two independent dominant fertility restorer (Rf) genes have been discovered, sequenced, and found tightly linked to a SCAR marker (Hasnunnahar et al, 2012). More recently, through an RNA-seq approach, further genes and pathways related to MS in eggplant have been identified (Yang et al, 2018b;Li et al, 2019a). However, the molecular mechanism of MS is not yet fully understood and further effort is needed to integrate MS into various eggplant genetic backgrounds through MAS.…”
Section: Future Outlookmentioning
confidence: 99%